Social Media Strategies for Luxury Brands: Navigating Brand Equity, Consumer Engagement, and Digital Challenges - Lee, Galvin Kuan Sian (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The intersection of social media and luxury branding presents a paradox: luxury thrives on exclusivity, while digital platforms are designed for visibility and participation. This narrative literature review synthesises studies published between 2010 and 2025 to examine how luxury brands navigate this paradox. Three key domains are explored: the role of social media in shaping brand equity, the evolving mechanisms of consumer engagement, and the digital challenges unique to the luxury sector. The review finds that while social media strengthens brand image through symbolic storytelling and aesthetic immersion, it has a more limited role in building brand awareness. Personalisation and co-creation strengthen emotional bonds and loyalty, though overuse risks prestige dilution. Technological innovations such as AR, VR, and AI offer new experiential frontiers but require alignment with the brand’s symbolic capital. This study contributes a multidimensional framework for understanding digital luxury branding and highlights managerial imperatives for balancing visibility with exclusivity. Future research is urged to explore generational and cultural variances, integrate stronger theoretical foundations, and address the tension between consumer empowerment and brand control in increasingly participatory environments.